(untitled) (Kohesi: Jurnal Sains dan Teknologi, 2025)
Indonesia, as an archipelagic country, has relatively high tidal characteristics due to the influence of the Indian Ocean, the Pacific Ocean, and its position along the equator. Padang City, located on the west coast of Sumatra, is vulnerable to extreme climate, flooding, and weather changes caused by the interaction of tides, rainfall, and topographic conditions. Tides affect sea level height, rainfall patterns, and river discharge, which can lead to flooding, especially with a less optimal drainage system. This study aims to determine the effect of tidal conditions on flooding and the effect of rainfall intensity on flooding in Padang City from 2020 to 2024. This research employs a quantitative method using secondary data obtained from the Meteorological, Climatological, and Geophysical Agency (BMKG) of Teluk Bayur Maritime and the Central Bureau of Statistics (BPS) of Padang City. The research began by processing the data using Microsoft Excel and SPSS to generate graphic plots, and then the data were further processed with the Surfer application to produce contour maps of Padang City. The results show a positive and significant correlation between rainfall intensity and flooding. The Pearson correlation analysis indicates a positive and significant relationship between rainfall and flood events. In contrast, the correlation between maximum sea level height and flood events shows a Pearson correlation coefficient of 0.025 with a significance value Sig. (2-tailed) = 0.298, meaning there is no significant relationship. Similarly, the correlation between minimum sea level height and flood events results in a value of 0.009 with a significance value Sig. (2-tailed) = 0.699, which is very weak and statistically insignificant, indicating no meaningful relationship between minimum sea level height and flood events.